Strategi Pemasaran Program Yayasan Ranu Welum Sebagai Non Governement Organization (NGO) Lingkungan Hidup di Kalimantan Tengah - Yoki Yohandi; Lelo Sintani; Meitiana Meitiana (Edunomics Journal, 2023)
In general, non-government organizations (NGOs) are known as grassroots organizations with unconventional, unique movements and often have bottom-up movements with programs that tend to be thematic and adapt to the surrounding circumstances. Even though they are not involved much in marketing activities, NGOs themselves cannot be separated from various marketing techniques. This is unavoidable because the thematic nature of programs that are carefully planned by the implementing NGO must be promoted to stakeholders (if needed) and potential donors, which will then be forwarded to the targets of the prepared programs. This study aims to describe the program marketing strategy that has been implemented by the Ranu Welum Foundation as a representative of environmental NGOs in Central Kalimantan and to design a generic strategy for program marketing based on their strengths and weaknesses as well as the opportunities and threat experienced. The research method is carried out with a qualitative approach, namely by conducting participatory observations and case studies in the form of a literature study on reports and analyzed using the SWOT matrix. The results show that the Ranu Welum Foundation as one of the environmental NGOs in Central Kalimantan, calculated using the SWOT matrix, implements an aggressive strategy in which environmental NGOs in Central Kalimantan use all available strengths and opportunities to attract people from various walks of life, especially rural communities, to become the target as well as the key figure of the marketed programs. The participation of NGO staff, especially field staff, is also a strategy that NGOs rely on to maintain consistency in the marketing of programs that have been implemented.